Efektivitas Penggunaan Model Pembelajaran Berbasis Masalah (PBM) terhadap Hasil Belajar Fisika Siswa SMAN 9 Lubuklinggau - Eka Maryam (University of Bengkulu, 2018)
ABSTRACT [The Effectiveness of Using a Model Problem-based Learning (PBL) to the Results of Physics Learning on High School Students 9 Lubuklinggau]. The objective of this study was to determine the effectiveness of the use of problem-based learning model. The research method used experiments with the form of Nonequivalent Control Group Design. The sample in this research is the students of class XI A and class XI B SMA N 9 Lubuklinggau City which amounted to 50 students. The technique of collecting data in this research is a test. The test is in the form of pretest and finally test (posttest). The purpose of holding initial and final tests to determine the effectiveness of Physics learning with PBM model and conventional learning. The test instrument that was made before the test was tested was done by panelists test using Intracorelation class coefficient (ICC). Data analysis technique used in this research is t-test. The results showed that there are differences in student learning outcomes taught with Problem-Based Learning model (PBM) with students taught with conventional learning model. The difference can be seen in the result of t-test which yields t-count> t-table (3,98> 2.01). The effectiveness of using the PBM model in the experimental class is 13.5% better than in the control class. Keywords: Effectiveness; model; PBL; learning outcomes.